Rancang Bangun Aplikasi I-Traffic Pada Dinas Perhubungan Surakarta Berbasis Android - Deni Saputri; Widyo Ari Utomo (Sekolah Tinggi Manajemen Informatika dan Komputer AUB - Indonesia, 2017)
Society in the region of Surakarta see traffic conditions by accessing the CCTV at official website of Department of Transportation. To access this website requires a fast and stable connection. As well as fulfilling the needs of traffic information society yet would be sure of. With the Application Architecture I-Traffic on the Department of Transportation Surakarta based Android can be a solution in fulfilling information needs traffic conditions in the region of Surakarta.This architecture is designed using the method Waterfall with a data structure (Data Flow Diagram), the software used is Apache Cordova using a programming language, PHP, HTML and Javascript and MySQL as the database. Application Architecture I-Traffic on the Department of Transportation Surakarta can provide information and traffic conditions using technology Geolocation so that capable of displaying dots coordinates occurrence constraints on a highway. As well as the public can play an active role in providing the report traffic conditions according the approval of the Department of transportation officer. Keywords: traffic information, the Department of transportation of Surakarta, Apache Cordova